Pelatihan Tari Bali Kekebyaran, Tari Panyembrama Dan Margapati Siswa-Siswi SMK N 8 Surakarta - Ni Nyoman Wati (Abdi Seni, 2016)
Community service activities is a routine agendawhich was held by universities throughout Indonesia as one element of Tri Dharma college. This time the activity is carried out by NI Nyoman Wati ISI Surakarta dance lecturer for three months with student trainees Vocational School District 8 Surakarta. The material taught is: two types of Balinese dance that consists of: dance groups such as dance Panyembrama daughter as a welcome to the guests. Dance dance dance Margapati is a type of manly men who usually danced a single, gestures depicting lion in prey. In this training Margapati dance groups presented with the intention of causing an element of novelty in its presentation. Both dances are very popular in Balinese society, proved up to now still exist. Due to the high interest of the trainees so that they can understand andmeragakan that both dance correctly. The author hopes the experience gained in the training of students can be practiced in the community in need. Key words : Dance Training Panyembrama and Margapati self-development tools